THE DOI PERAN SEKOLAH DALAM MENGINTERNALISASI PROFIL PELAJAR PANCASILA DI LINGKUNGAN SMK AISYIYAH PALEMBANG - Putri Adiya Pramesti, Ayu; Chotimah, Umi (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to describe the efforts of SMK Aisyiyah Palembang in realizing the Pancasila Student Profile (PPP) through a learning approach and school culture. The approach used is descriptive qualitative with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the school integrates PPP values ​​such as religiosity, mutual cooperation, independence, critical thinking, and creativity in intracurricular, co-curricular, extracurricular activities, and daily habits. Programs such as One Day One Juz, Clean Friday, contextual learning, and student involvement in organizations are effective media in shaping the character of students. However, the implementation still faces obstacles, such as low participation of some students and the need for program innovation. This study concludes that the success of PPP implementation depends on the synergy between teachers, students, and the school as a whole. With a consistent and reflective approach, schools can be a strategic place in shaping the character of Indonesian students who are noble, independent, and globally competitive.